The future of SA-UK trade in a post-Brexit world. Issue 2 (2nd April 2020) - Ismail, Faizel; Grunder, Jay
ABSTRACT: This article discusses the relationship between South Africa (SA) and the United Kingdom (UK) in the post-Brexit era. An overview of the history of the SA-UK relationship until the negotiation of the SACU + M-UK agreement in 2019 is provided. At least two scenarios in a post-Brexit UK-European Union trade relationship are analysed and their implications for SA-UK relations are discussed. The article explores the question: will the post-Brexit period be characterised by an increasingly aggressive Britain striving to re-assert its power in the world, or shall the world see a new idealist Britain seeking to increase cooperation in its own region and globally? The article argues that South Africa should expect the first scenario but also prepare to influence the UK towards the second scenario.